Knowledge, attitude, practice and associated factors towards COVID-19 and its prevention measures among residents of Mekelle City, Tigray Region, Northern Ethiopia: a community-based cross sectional study. - Kiros, Marshet; Gebru, Shifare Berhe; Tewelde, Bisrat (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: The emerging respiratory disease known as the novel coronavirus disease (COVID-19) became a global concern and was declared as a global health emergency by the World Health Organization (WHO) on March 11, 2022. This study aimed to assess knowledge, attitude, and practice and associated factors toward COVID-19 and its prevention measures among residents of Mekelle city, Tigray, Northern Ethiopia. Subject and methods: A community-based cross-sectional study was conducted among 604 residents of selected kebelles in Mekelle city, Tigray region from April to February 2022. A structured questionnaire and observation check list were used to collect the data. Multivariable logistic regression analysis was used with SPSS version 25 to identify factors associated with the outcome variables. Results: A total of 604 residents were participated in the study with 100% response. Among the total study participants (n = 604), 74.2%, 58.8%, and 39.2%, of them had good knowledge, a positive attitude, and good practice toward COVID-19 and its preventive measures, respectively. Results from the multivariate analysis showed that age, level of education, and family size were found to be significantly associated with good knowledge of study participants toward COVID-19. Additionally, occupation, family size, income level, and having knowledge about COVID-19 were significant factors associated with the attitude of the study participants toward COVID-19. Moreover, practice of study participants to prevent COVID-19 was also significantly associated with educational status, occupation status, income level, and having a positive attitude about the practice toward COVID-19 prevention. Conclusion: This study result revealed that the study participants' knowledge and attitude regarding COVID-19 were good. However, their practice toward COVID-19 and its preventive measure was poor, which will affect combating the pandemic. Therefore, continuous and effective public health education programs, community mobilization, law enforcements, and breaking siege and allowing all types of humanitarian aids in the region are urgently needed to improve knowledge, attitude, and practices toward COVID-19 and its preventive measures among the residents.